2019
DOI: 10.1002/dvdy.78
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin‐induced ductal formation in salivary gland self‐organization model

Abstract: Background: Recent advances in tissue regeneration approaches including 3D organoids, were based on various 3D organogenesis models. However, 3D models are generally technique-sensitive and time-consuming. Thus, we utilized an existing model of submandibular salivary gland (SMG) to modify a simple and highly reproducible in vitro 3D culture model of primary SMG cells self-organization into a well-developed cell spheroid inside Matrigel substrate. We used this model to observe the collective multicellular behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…Hydrogel substrate with different mechanical stiffness could effectively alter the cellular behavior of mesenchymal stem cells and change their future lineages (Engler et al 2006). Studies from our group effectively utilized different hydrogel systems to recapitulate and modulate the development and growth of soft tissue (Taketa et al 2015; Sathi et al 2017; Farahat et al 2019) and hard tissue (Sathi et al 2015). In the latter work, we cultured mouse embryonic femur bones inside an agarose hydrogel with different mechanical stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogel substrate with different mechanical stiffness could effectively alter the cellular behavior of mesenchymal stem cells and change their future lineages (Engler et al 2006). Studies from our group effectively utilized different hydrogel systems to recapitulate and modulate the development and growth of soft tissue (Taketa et al 2015; Sathi et al 2017; Farahat et al 2019) and hard tissue (Sathi et al 2015). In the latter work, we cultured mouse embryonic femur bones inside an agarose hydrogel with different mechanical stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The first induces PSCs to differentiate towards oral ectoderm in a 3D culture enriched with several growth factors and cytokines to promote the salivary gland morphogenesis [ 125 ]. The second requires the incubation of salivary gland progenitors in 3D scaffolds to promote the formation of the gland structure thanks to several growth factors [ 126 , 127 ]. Salivary organoids have also been obtained thanks to magnetic 3D bioprinting using DPSCs and neural crest-derived mesenchymal stem cells as “ink” [ 128 ].…”
Section: Overview Of Different Types Of Dental Stem Cellsmentioning
confidence: 99%
“…Recent studies have found that stem/progenitor cells isolated from the salivary gland can be expanded and differentiated to generate organoids capable of restoring gland function in vivo (Fig. 2A) (Farahat et al 2019; Sui et al 2020). These processes are controlled by the treatment of numerous growth factors, including EGF, FGFs, and TGF-β (Farahat et al 2019; Sui et al 2020).…”
Section: Construction Of Oral Organoidsmentioning
confidence: 99%
“…2A) (Farahat et al 2019; Sui et al 2020). These processes are controlled by the treatment of numerous growth factors, including EGF, FGFs, and TGF-β (Farahat et al 2019; Sui et al 2020). The artificial niche promoted the development of salivary gland organoids, as indicated by the expression of differentiation markers, structure formation, and response to neurotransmitters in vitro.…”
Section: Construction Of Oral Organoidsmentioning
confidence: 99%